Student Team Achievement Division with Problem-Based Learning-Based Worksheet (LKPD): Improving Students' Math Affection and Cognition - Taruna Ruti Dermawan; Eni Titikusumawati; Wawan Kurniawan (Institut Agama Islam Negeri (IAIN) Salatiga, 2023)
This study aims to determine the improvement of mathematics learning outcomes through the application of the Students Team Achieviement Division (STAD) learning model with Problem Based Learning (PBL) based LKPD on set material in class VII A students of SMP Islam Al Azhar 18 Salatiga. This research is class action research conducted in two cycles through the steps of planning, implementation, observation, and reflection. Data collection techniques were tests, questionnaires, observation sheets, and documentation. The data were analyzed by comparing the achievement with the Minimum Completeness Criteria (KKM) and marked by an increase in classical completeness in each cycle. The results showed that the application of the STAD learning model with PBL-based LKPD can improve the learning outcomes of set material. This increase in learning outcomes is based on data on student learning outcomes with an average class in cycle I of 73.54 with 10 students completed (41.66%) and 14 students not completed (58.33%), then increased in cycle II with an average class of 87.08 with 21 students completed (87.5%) and 3 students not completed (15.5%). The research stopped in cycle II because it had reached the success indicator, namely ≥85% of the total number of students in one class obtained a score that met the KKM, namely ≥80.